Stellar occultations by bodies in the outer solar system at the South African Astronomical Observatory - Genade, Anja (Department of Astronomy, 2019)
Information on the origin and evolutionary processes of the Solar System is harbored by primitive bodies called trans-Neptunian objects (TNOs). Their preserved state is due to these bodies having orbits at and beyond that of Neptune, as this specific area is considered to be the least thermally modified in the Solar System and could contain a large population of primordial remnants. These archaic remnants not only provide us with information on our infant Solar System, but also improve our understanding of extrasolar planetary formation processes. Stellar occultations by TNOs enable the determination of sizes and shapes with kilometric accuracy (confining albedos, leading us to compositions and densities), the detection of atmospheres down to pressures of a few nanobars, as well as an investigation of the immediate vicinity of the target body (indicating the presence of rings, satellites, jets, comas). These TNOs roam the icy outskirts of our Solar System which, together with their small sizes, make them faint and their stellar occultations short-lived. With a duration ranging from a couple of seconds for small bodies up to a few hundreds of seconds for the larger TNOs, specific imaging cameras combined with Global Positioning devices and optical telescopes, ensure the fast-cadence capture of these events with microsecond timing accuracy. This high-time resolution observing in combination with the relative speed of the star and the occulting body ensures accurate results with resolutions down to the kilometriclevel, which overthrows the resolvability of ground-based telescopes and rivals that of space probes. Here, we present work done by the South African Astronomical Observatory (SAAO) stellar occultation observing program during the period of July 2016 - July 2017. Specifically, we describe the telescopes, instruments and data analysis pipelines that are used for the SAAO stellar occultation program. The stellar occultation results are obtained from the slightly modified, data reducing SHOC pipeline as originally developed by Dr. Marissa Kotze. The SHOC pipeline laid the groundwork for two additional pipelines to be developed and therefore the MORIS instrument on the 3-m IRTF as well as the FLI autoguider cameras mounted on multiple 1-m LCO telescopes are included to provide many opportunities to observe the predicted stellar occultations. These pipelines include reduction features, correct and accurate derivation of timing information, optimization of the signal-to-noise ratio (SNR) through aperture corrected photometry and most important, provide the user with light curve plots of the point sources. The light curves are normalized and individually analyzed for any signs of a positive stellar occultation detection while testing the effects of reduction on the SNR. This is followed by checking the statistical distribution of the data as well as determining a few values for the line-of-sight optical depth. Instrumental deadtimes for the LCO guider cameras are calculated to effectively determine and use time allocated through proposals. Finally, a single positive stellar occultation by Orcus was observed on 7 March 2017 from two separate sites. Here, chord length calculations as well as timing offsets are calculated from the normalized light curves which led to a possible detection of both Orcus and Orcus’s satellite, Vanth. An in depth discussion is provided to justify this reasoning. This thesis serves to characterize and consolidate the now well-established program of stellar occultation observations at the SAAO.